Effect of co-trimoxazole prophylaxis on morbidity and mortality of HIV-exposed, HIV-uninfected infants in South Africa: a randomised controlled, non-inferiority trial. Issue 12 (December 2019) - Daniels, Brodie; Coutsoudis, Anna; Moodley-Govender, Eshia; Mulol, Helen; Spooner, Elizabeth; Kiepiela, Photini; Reddy, Shabashini; Zako, Linda; Ho, Nhan T; Kuhn, Louise; Ramjee, Gita
Summary: Background: WHO guidelines recommend co-trimoxazole prophylaxis for HIV-exposed, HIV-uninfected infants. These guidelines date back to an era in which HIV testing of infants was impossible and mothers had poor access to antiretroviral treatment. To determine whether this guideline requires revision in the current era of effective prevention of mother-to-child transmission and early infant diagnosis programmes, we aimed to investigate whether receiving no co-trimoxazole prophylaxis is inferior to receiving co-trimoxazole prophylaxis in the resulting incidence of grade 3 or 4 common childhood illnesses or mortality in breastfed HIV-exposed, HIV-uninfected infants. Methods: We investigated our aim in a randomised controlled, non-inferiority trial. We enrolled the HIV-negative infants of mothers living with HIV who were actively involved in transmission prevention programmes in two clinics in Durban, South Africa. Infants were included in the study if they were breastfeeding at the screening and enrolment visits, and their mother was planning to breastfeed for at least 6 months; were a singleton birth and had a birthweight of 2 kg or more; had no clinically observed genetic disorders; and had no serious illnesses and had not received antibiotics or traditional medications (such as herbal remedies). Infants were randomly assigned (1:1) to receive co-trimoxazole or no co-trimoxazole. In the co-trimoxazole group, infants received the drug until all exposure to HIV had ceased (ie, 6 weeks after last exposure to breastmilk) and the infant was confirmed to be uninfected with HIV. The drug was administered by mothers in once-daily regimens of 20 mg trimethoprim and 100 mg sulfamethoxazole orally (age <6 months or bodyweight <5 kg), or 40 mg trimethoprim and 200 mg sulfamethoxazole orally (age >6 months or bodyweight >5 kg). Clinical and laboratory staff always remained masked to group assignment, but mothers and study counsellors were not. Infants and their mothers attended study visits at ages 6 weeks (for enrolment and randomisation), 10 weeks, 14 weeks, and then monthly from 4 to 12 months. Our primary outcome was the incidence of grade 3 or 4 common childhood illnesses (pneumonia or diarrhoea) or mortality in breastfed HIV-exposed, HIV-uninfected infants by age 12 months. A non-inferiority bound of 5% was used. The study is registered with the Pan African Clinical Trials Registry, number PACTR201311000621110, and the South African National Clinical Trials Registry, number DOH-27-0614-4728. Findings: We screened 1570 mother–child pairs for study enrolment, from whom (78%) eligible infants were enrolled into the study between Oct 16, 2013, and May 23, 2018. Of the infants enrolled, 611 (50%) were randomly assigned to the co-trimoxazole group and 609 (50%) were randomly assigned to the no co-trimoxazole group. One (<1%) infant in the no co-trimoxazole group was excluded from the analysis of the final outcomes for having received traditional medicine (which only became apparent after randomisation); therefore, 611 (50%) infants in the co-trimoxazole group and 608 (50%) infants in the no co-trimoxazole group were included in the final intention-to-treat analysis. 136 (22%) infants in the co-trimoxazole group and 139 (23%) infants in the no co-trimoxazole group did not complete the 12-month study visit, predominantly because of loss to follow-up (93 [15%] infants in the co-trimoxazole group; 90 [15%] infants in the no co-trimoxazole group). The cumulative probability of the composite primary outcome was 0·114 (95% CI 0·076 to 0·147; 49 events) in the co-trimoxazole group versus 0·0795 (0·044 to 0·115; 39 events) in the no co-trimoxazole group. The risk difference (no co-trimoxazole group minus co-trimoxazole group) was −0·0319 (–0·075 to 0·011), meaning that the risk was around 3 percentage points lower in the no co-trimoxazole group on the additive scale. Interpretation: We can conclude that no co-trimoxazole is not inferior to daily co-trimoxazole among breastfed HIV-exposed, HIV-uninfected infants whose mothers are accessing a prevention of mother-to-child transmission programme in an area unaffected by malaria. We therefore believe that WHO should revise the co-trimoxazole guidelines for HIV-exposed, HIV-uninfected infants in areas unaffected by malaria. Funding: HIV Prevention Research Unit of the South African Medical Research Council and the Family Larsson-Rosenquist Foundation.